Human Trafficking : Definitions, Data, and Determinants - Winkler, Stephen J. (World Bank, Washington, DC, 2021)
This paper reviews the literature on human trafficking with a focus on understanding how it is defined and measured and what factors contribute to or constrain the prevalence of human trafficking. It finds a growing consensus among scholars on the importance of distinguishing between coercive and non-coercive activity to prevent inflated statistics and misguided programs and policies. The paper summarizes the individual, societal, and institutional explanations for the prevalence of human trafficking. However, it also shows how imprecise definitions of human trafficking and a lack of data and analyses contribute to widespread uncertainty regarding the relative effects of anti-trafficking policies such as border and migration policies or laws on prostitution. The paper suggests several avenues for future research that could help clarify these policy debates and emphasizes the need for additional micro-level data collection and analysis.